2018
DOI: 10.5194/acp-18-17177-2018
|View full text |Cite
|
Sign up to set email alerts
|

Two years of online measurement of fine particulate nitrate in the western Yangtze River Delta: influences of thermodynamics and N<sub>2</sub>O<sub>5</sub> hydrolysis

Abstract: Abstract. Particulate nitrate contributes a large fraction of secondary aerosols. Despite understanding of its important role in regional air quality and global climate, long-term continuous measurements are rather limited in China. In this study, we conducted online measurement of PM2.5 (particulate matter with diameters less than 2.5 µm) nitrate for 2 years from March 2014 to February 2016 using the Monitor for AeRosols and Gases in ambient Air (MARGA) in the western Yangtze River Delta (YRD), eastern China,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 60 publications
(81 reference statements)
4
49
0
Order By: Relevance
“…Overall, the average POH(HONO) during 8:00-16:00 LT is 0.90 ± 0.27 ppb/h, more than twice the value of POH(O3), the mean value of which is 0.41 ± 0.25 ppb/h. The impressive role of HONO in the atmospheric oxidizing capacity should benefit photochemical ozone production (Ding et al, 2013;Xu et al, 2017;Xu et al, 2018), new particle formation and secondary aerosol formation (Xie et al, 2015;Sun et al, 2018) in Nanjing, the western YRD region.…”
Section: Observation Overviewmentioning
confidence: 99%
“…Overall, the average POH(HONO) during 8:00-16:00 LT is 0.90 ± 0.27 ppb/h, more than twice the value of POH(O3), the mean value of which is 0.41 ± 0.25 ppb/h. The impressive role of HONO in the atmospheric oxidizing capacity should benefit photochemical ozone production (Ding et al, 2013;Xu et al, 2017;Xu et al, 2018), new particle formation and secondary aerosol formation (Xie et al, 2015;Sun et al, 2018) in Nanjing, the western YRD region.…”
Section: Observation Overviewmentioning
confidence: 99%
“…Fine particulate matter, with an aerodynamic diameter smaller than 2.5 µm (PM 2.5 ), which impacts human health and visibility negatively (Cao et al, 2012;Zhang et al, 2017;Malm et al, 2004), has been considered to be one of the main air pollutants in China (He et al, 2001;Yao et al, 2002;Sun et al, 2006;Pathak et al, 2009;Zhang et al, 2015;. To tackle this great challenge, China has been implementing the "Action Plan for Air Pollution Prevention and Control" (i.e., the so-called national "Ten Measures of air") in several developed critical regions since 2013 (Sheehan et al, 2014;Wang et al, 2017;Liu et al, 2018Liu et al, , 2019Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies reported the change of PM2.5 and its chemical components in some YRD cities in a short period, e.g. 2-3 years (Wang H. et al, 2016;Sun et al, 2018), however, so far there is a lack of long-term observational study with 25 comprehensive measurements covering the entire period of national "Ten measures" period, i.e. 2013-2017, in this region.…”
Section: Introductionmentioning
confidence: 99%
“…sulfate (SO4 2-), nitrate (NO3 -), ammonium (NH4 + ), potassium(K + ), 15 and calcium (Ca 2-), etc.) has been measured since 2013 (Xie et al, 2015;Sun et al, 2018;Wang et al, 2018;Shen et al, 2018). Details of the data, including instrumentation, measurement period, and data coverage, used in this study are given in Table S1 in the Supporting Information (SI).…”
Section: Brief Introduction To the Sorpes Station And Instrumentationsmentioning
confidence: 99%
See 1 more Smart Citation